Algeria : Selected Issues Paper. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper studies the main sources for growth in Algeria within a cross-country analysis and draws policy recommendations to support faster growth. In Section 1, a growth accounting exercise framework has been explained, and in Section 2, the determinants for growth are identified. This study examines the factors behind the recent increase in inflation and the policies that should be implemented to bring inflation back to the level targeted by the monetary authorities. Two approaches used to explore the determinants of inflation were discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet